IIUM Pre-sessional students’ Perceptions of Academic Listening Competence and their English Listening Problems - Abdul Malik, Faridah; Othman, Khairiah (2014)
Listening comprehension is a crucial part of both first and second language communication and it is vital for one’s academic success. Yet, with the removal of a listening test from the English Placement Test examination at CELPAD, the development of listening skill seems to have been sidelined. This study investigated whether or not listening comprehension is a problem for pre-university students at IIUM. Specifically, this study explored the students’ perceptions on the listening problems that they encountered as well as the importance of listening competence. It also examined if the problems faced by learners were different according to their proficiency levels and ethnic backgrounds. To this end, questionnaires were administered to 307 pre-university students taking the IELP at CELPAD. The findings of the study indicate that these learners feel that listening competence is important for academic success but they do not regard it as the most difficult skill to master. However, fast speed of delivery and accents are still problematic to them and the less proficient learners seem to face a wider range of problems than their more proficient counterparts. It is recommended that the listening test component be reintroduced into the curriculum especially for learners at the lower levels.